China’s alternative remittance system: channels and size of "hot money" flows - Li, Jianjun (Crime, law and social change, 2012)
As the Federal Reserve engages in its second quantitative easing monetary policy, global emerging economies will suffer a shock of 600 billion dollars of funds. What is more, the Federal Reserve will continue to follow a policy of quantitative easing, and some of these excess dollars will flow into China and other emerging markets through alternative remittance channels. Excess liquidity may become "hot money" that disrupts the capital market and intensifies macroeconomic instability. This paper first studies the basic operational principle of the alternative remittance system as well as its actual operation in China. After examining domestic and foreign scholars’ research methods with respect to the alternative remittance system, we estimate the size of hot money flowing through the alternative remittance system in China by building an Error Correction Model and analyze the difference between the result we calculate from it and the actual amount. Then based on this, we put forward comprehensive policy recommendations to regulate and supervise the alternative remittance system in China in terms of underground banks, trade fraud and foreign investment activity.